Immunological Monitoring in the System of Epidemiological Surveillance of Brucellosis in Siberia - N. O. Kiseleva; V. I. Dubrovina; K. M. Korytov; A. B. Pyatidesyatnikova; D. D. Bryukhova; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика)
Relevance. Brucellosis is a particularly dangerous zoonotic infectious disease, characterized by multiple lesions of organs with a high potential for transition to a chronic forms. In recent years a situation on brucellosis remains unstable epidemiologic in the Russian Federation.Aim of study. The conduction of screening research in people living in brucellosis-unfavorable territories the cellular and humoral immunity indicators using antigen-specific in vitro tests.Materials and Methods. The immunologic monitoring of volunteers from brucellosis-unfavorable territories of the Republics of Tyva (Khandagaiti village, Ovurskiy district, n=317) and Altai (Kosh-Agach village, Kosh-Agachskiy district, n=150), and employees from the institute (n=30). The research included determination of the presence of specific antibodies of class G to the brucellosis pathogen, concentrations of cytokines (IFN-γ, IL-2, etc.) and major classes of immunoglobulins in blood serum, spontaneous and antigen-induced production of cytokines by blood cells using ELISA, and immunophenotyping of blood lymphocytes by flow cytometry.Results and discussion. Among all examined volunteers from unfavorable territories, specific antibodies to the brucellosis pathogen were detected in 113 people (24.2%). The IL-2 stimulation index in the seronegative volunteer group was found to be 2.3 times higher compared to the seropositive group. Positive results of the level of antigen-induced production (LAP) of IFN-γ were observed in 48 (16.8%) volunteers, which indicates the presence of T-lymphocytes with antigen-specific receptors to the brucellosis pathogen. IFN-γ’s LAP was found to be 8.3 times higher in volunteers with specific antibodies to the brucellosis pathogen. Humans diagnosed with brucellosis and vaccinated volunteers showed an increase in the stimulation ratio of T-lymphocyte activation markers (CD25 and HLA-DR) >51%.Conclusion. Thus, the effectiveness of antigen-specific in vitro tests for assessing the formation of postvaccinal immunity and diagnosis of brucellosis infection was demonstrated. The introduction of annual immunologic monitoring of specific immunity against brucellosis in humans living in brucellosis-unfavorable territories of Siberia makes it possible to increase the effectiveness of the complex of measures to ensure epidemiological surveillance of brucellosis.